Nogle realistiske bemærkninger til Piagets læringsteori - Thomas Aastrup Rømer (Utbildning & Demokrati)
I want to reflect on some problematic aspects of the use of Piaget’s learning theory. In Denmark, education has been deeply influenced by piagean ideas of learning. My reflection concerns the understanding of Piaget’s concept of adaptation – and of its two underlying processes, assimilation and accommodation. I argue that these processes are often either too separated from each other or tend to forget about the external world. In addition, I propose a reading of the concluding chapter of Piaget’s book The Construction of Reality in the Child from 1954. I present two overlapping interpretations, both of which draw on aspects of Piaget’s work that connects his work to philosophical realism and a dynamic concept of Bildung. The aim is to argue that Piaget’s categories of learning are related to objects and things to a much greater extent than previously assumed.